In first equation you replace m with the value of m from 2nd equation
-10p+3=5p+8
-15p=5
p=-5/15=-1/3
Now you replace the value of p in the 1st equation
m=5(-1/3)+8
3m=-5+24
3m=19
m=19/3
2007-10-10 19:34:13
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Substitution simply asks you to solve for one of the variables in either of the equations and then use that answer and plug it in the other equation.
For example
m has already been solved for you so you just plug in its value in the other equation
m = 5p + 8
m = -10 + 3
They tell you that m is equal to both of this equations so just replace one of the m's with the other other
m = m
therefore
5p + 8 should equal -10p + 3
5p + 8 = -10p + 3
15p = -5
p = -1/3
After solve for p you can plug it in either equation to obtain the exact value of m.
m = 5(-1/3) + 8
m = -5/3 + 24/3
m = 19/3
2007-10-10 19:40:48
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
from the answers that i can see from the time i am posting,
they are solving this SIMULTANEOUS EQUATION by method of SUBSTITUTION.
i will give another alternative method called ELIMINATION.
1. u line it up one over the other to compare like this:
m=5p+8 (let this be equation 'z')
m=-10p+3 (let this be equation 'y')
as u can see, there is already a common factor of m in both equations so it is easiest to eliminate m.
2. minus equation 'y' from equation 'z' like this:
m=5p+8
- m=-10p+3
--------------------
0=15p+5
--------------------
3. rearrange to get p=-1/3
15p+5=0
15p=-5
p=-5/15
p=-1/3
4. knowing p=-1/3, we get m. we can insert in either equations for the same answer will be found.
m=5(-1/3)+8
m=19/3
this should give you the foundations to understand how SIMULTANEOUS EQUATIONS work. hope u wont have any problems after this. this is only the basics of a lovely world of MATHS out there waiting to studied.
=)
2007-10-10 20:08:06
·
answer #3
·
answered by pplcallmeibs 1
·
0⤊
0⤋
Let m=5p+8--->(1)
Let m=-10p+3--->(2)
From (2) 5p+8=-10p+3
15p=-5
p=-1/3
p=-1/3,From (1) m=5(-1/3)+8
=19/3
2007-10-10 21:16:37
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
m=5p+8
m=-10p+3
5p + 8 = -10p + 3
15p = -5
p = -5/15
=> p = -1/3
m = 5p + 8
m = 5(-1/3) + 8
m = -5/3 + 8(3/3)
m = -5/3 + 24/3
=> m = 19/3
2007-10-10 19:31:13
·
answer #5
·
answered by The Monkey's Paw 2
·
0⤊
0⤋
5 p + 8 = - 10 p + 3
15 p = - 5
p = - 5 / 15 = - 1 / 3
m = - 5 / 3 + 8
m = - 5 / 3 + 24 / 3
m = 19 / 3
m = 19 / 3 , p = - 1 / 3
2007-10-14 06:14:49
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
m = 5p + 8
m = -10p + 3
5p + 8 = -10p + 3
15p + 8 = 3
15p = -5
p = -1/3
2007-10-10 19:31:09
·
answer #7
·
answered by supensa 6
·
0⤊
0⤋
p=-1/3
m=19/3
2007-10-10 19:41:48
·
answer #8
·
answered by pooh 2
·
0⤊
0⤋